Multilaboratory Comparison of Pneumococcal Multiplex Immunoassays Used in Immunosurveillance of Streptococcus pneumoniae across Europe - Bob Meek (American Society for Microbiology, 2019)
ABSTRACT Surveillance studies are required to estimate the impact of pneumococcal vaccination in both children and the elderly across Europe. The World Health Organization (WHO) recommends use of enzyme immunoassays (EIAs) as standard methods for immune surveillance of pneumococcal antibodies. However, as levels of antibodies to multiple serotypes are monitored in thousands of samples, a need for a less laborious and more flexible method has evolved. Fluorescent-bead-based multiplex immunoassays (MIAs) are suitable for this purpose. An increasing number of public health and diagnostic laboratories use MIAs, although the method is not standardized and no international quality assessment scheme exists. The EU Pneumo Multiplex Assay Consortium was initiated in 2013 to advance harmonization of MIAs and to create an international quality assessment scheme. In a multilaboratory comparison organized by the consortium, agreement among nine laboratories that used their own optimized MIA was assessed on a panel of 15 reference sera for 13 pneumococcal serotypes with the new WHO standard 007sp. Agreement was assessed in terms of assay accuracy, reproducibility, repeatability, precision, and bias. The results indicate that the evaluated MIAs are robust and reproducible for measurement of vaccine-induced antibody responses. However, some serotype-specific variability in the results was observed in comparisons of polysaccharides from different sources and of different conjugation methods, especially for serotype 4. On the basis of the results, the consortium has contributed to the harmonization of MIA protocols to improve reliability of immune surveillance of Streptococcus pneumoniae. IMPORTANCE Serology of Streptococcus pneumoniae is challenging due to existence of multiple clinically relevant serotypes and the introduction of multivalent vaccines in national immunization programs. Multiplex immunoassays (MIAs) are applied as high-throughput cost-effective methods for serosurveillance, and yet laboratories use their own protocols. The aims of this study were to assess the agreement of results generated by MIAs in different laboratories within the EU Pneumo Multiplex Assay Consortium, to analyze factors contributing to differences in outcome, and to create a harmonized protocol. The study demonstrated good agreement of results of MIAs performed by laboratories using controlled assays for determination of levels of vaccine-induced pneumococcal antibodies. The EU Pneumo Multiplex Assay Consortium is open to everyone working in public health services, and it aims to facilitate efforts by participants to run and maintain a cost-effective, reproducible, high-quality MIA platform.